Chemical Investigations on Algerian Mentha rotundifolia and Myrtus communis Essential Oils and Assessment of their Insecticidal and Antifungal Activities - Aouadi Ghozlene; Soltani Abir; Kalai Grami Leila; Ben Abada Maha; Haouel Soumaya; Boushih Emna; Chaanbi Manel; Elkahoui Salem; Hajlaoui Mohamed Rabeh; Mediouni Ben Jemâa Jouda; Taibi Faiza (Friends Science Publishers, 2021)
This work aimed to assess in vitro insecticidal and antifungal activities of Mentha rotundifolia and Myrtus communis essential oils against the red flour beetle (Tribolium castaneum) and three fungal species (Botrytis cinerea, Fusarium solani and Colletotrichum acutatum). Oxygenated monoterpenes presented the dominant group with 72.94 and 58.92% respectively for M. rotundifolia and M. communis essential oils. M. rotundifolia and M. communis essential oils composition was dominated by 72.94 and 58.92% of oxygenated monoterpenes, respectively. The determined lethal concentrations of mentha essential oils against T. castaneum adults revealed high toxicity respectively for fumigant and contact tests, LC50 = 0.113 μL cm-2 and LC50 = 32.71 μL L-1 air. However, common myrtle oil showed a weak fumigant activity (LC50 = 357.67 μL L-1 air) and no contact toxicity. Furthermore, M. rotundifolia essential oil showed a marked antifungal toxicity against all the fungal strains. The mycelial growth of the three fungal strains was completely inhibited at the concentrations of 0.33 μL L-1 by contact application and 8, 10 and 12 µL by fumigant application. M. communis essential oil displayed only a contact antifungal toxicity against B. cinerea at the concentration 21.33 μL L-1. Additionally, M. rotundifolia completely inhibited conidial germination of B. cinerea and F. solani, and significantly affected their morphology, with morphological modifications at the rate of 92.94 and 51.11% respectively. In light of in vitro tests results, the mentha essential oil appeared to be an excellent source of antifungal and insecticidal components and will allow the potential development of this species in the biological control of several pests and fungal diseases. © 2021 Friends Science Publishers